A Facile Synthesis of Organotin(IV) Carboxylates: Application as Single Source Precursor for Deposition of Tin Oxide Thin Films and Evaluation of Biological Activities. Issue 37 (2nd October 2018) - Butt, Arshad Farooq; Bhatti, Moazzam Hussain; Aamir, Muhammad; Ch, Muhammad Aziz; Tahir, Muhammad Nawaz; Sher, Muhammad; Ahmed, Mirza Jamil; Akhtar, Javeed
Abstract: Herein, we report synthesis of novel organotin(IV) carboxylates i.e; [(C6 H5 )3 Sn(C10 H14 NO3 )]B1 and [(C4 H9 )3 Sn(C10 H14 NO3 )]B2 by reacting triphenyltin hydroxide and bis (tributyltin) oxide with as‐prepared ligand 3‐cyclohexylcarbamoyl‐acrylic acidA under inert atmosphere. The as‐synthesized complexes were characterized by elemental analysis (CHNS), fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance spectroscopy( 1 H‐NMR, 13 C‐NMR) and mass spectrometry (EI‐MS). The structures of both as‐prepared tin complexesB1 andB2 were determined by single crystal X‐ray crystallography. Thermogravimetric analysis has shown single step decomposition of both these complexes. The as‐prepared complexes were used as single source precursor for the deposition of tin oxide thin films at 350 °C and 400 °C by aerosol assisted chemical deposition (AACVD) on bare and at 400 °C on carbon nanodots pre‐coated glass substrate. The as‐deposited thin films were characterized by powdered X‐rays diffraction (pXRD), field emission scanning electron microscope (FE‐SEM) and energy dispersive X‐rays spectroscopy (EDX). Furthermore, antimicrobial, anti‐oxidant and cytotoxicity studies of both complexes showed moderate to good biological activities. Thus, as‐prepared novel complexes have potential applications in materials as‐well as in medicinal chemistry. Abstract : We report the synthesis of organotin(IV) carboxylates i.e; [(C6 H5 )3 Sn(C10 H14 NO3 )] B1 and [(C4 H9 )3 Sn(C10 H14 NO3 )] B2 by reacting triphenyltin hydroxide and bis (tributyltin) oxide with as‐prepared ligand 3‐cyclohexylcarbamoyl‐acrylic acid under inert atmosphere, respectively.The complexes were used successfully as single source precursor (SSP) to deposit tin oxide thin films. The bioactivity of these complexes was also studied.